Answer:
5
Step-by-step explanation:
first term + (10-1)7=68
first term= 68- 63=5
Answer:
b
Step-by-step explanation:
Answer:
Dot 1. y = 3, x = 1
Dot 2. y = 6, x = 2
Dot 3. y = 12, x = 4
Dot 4. y = 18, x = 6
Step-by-step explanation:
Distance(m) = y
Time(s) = x
Therefore whatever is traveling at that speed is getting faster (A Perpetual Energy Producing Bullet) since at first it goes a = 3 Distance(m) and then duplicates its distance and Time traveled which makes sence. Then it does the same thing again! (∑²ᵇ⁽¹⁾) This is the mathematical equation that changes it. It basically means it takes a sum of the last number than multiplies it by itself to the power of (2ᵇ) and then to the power of 1 to finish off the equation. (∑²ᵇ⁽¹⁾) = ( (u x 2) x2) + c) = Infinite power looping then taking breaks in between to take a variable that was 2 last of itself and add that to the sum of the entire equation!
c = (u x 2)!
Hope this helps!
<u><em>Also can I have brainliest...</em></u>
Answer:
The teenagers spent 4.5 hours per week, on average, on the phone.
Step-by-step explanation:
We are given the following in the question:
Population mean, μ = 4.5
Sample mean,
= 4.75
Sample size, n = 15
Alpha, α = 0.05
Sample standard deviation, s = 2
First, we design the null and the alternate hypothesis
We use one-tailed(right) t test to perform this hypothesis.
Formula:
Putting all the values, we have
Now,
Since,
We accept the null hypothesis. Thus, the teenagers spent 4.5 hours per week, on average, on the phone. The sample contradicted the organization's claim.
The answer is 7.50%.
6 * 0.075 = 0.45.
6 - 0.45 = 5.55.